2017
DOI: 10.1111/hae.13198
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of health‐related quality of life of boys with severe haemophilia A in China: comparing on‐demand to prophylaxis treatment

Abstract: Child-reported CHO-KLAT scores were lower in boys with severe HA in China than reported in countries with access to full-dose prophylaxis. Boys reported higher HR-QoL scores than their parents. Small improvements in ASK scores were noted following the prophylaxis phase. These changes were only significant in the parent-reported CHO-KLAT scores. Longer term prospective clinical trials are needed in China to determine the impact of prophylaxis on HR-QoL in boys with severe HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 25 publications
3
29
1
1
Order By: Relevance
“…The generic measure of activity, the ASK, also provides supplementary information that enables the children in Jamaica to be compared with other studies. The reported mean score of 82.0 for Jamaican children in this study was slightly higher (better) than the mean from a Chinese sample with severe haemophilia (mean = 74.9 during on‐demand therapy) but lower (worse) than a Brazilian sample (median = 92.0) in which 70% of children had severe haemophilia . These data are consistent with the availability of clotting factor concentrates in the countries referenced.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The generic measure of activity, the ASK, also provides supplementary information that enables the children in Jamaica to be compared with other studies. The reported mean score of 82.0 for Jamaican children in this study was slightly higher (better) than the mean from a Chinese sample with severe haemophilia (mean = 74.9 during on‐demand therapy) but lower (worse) than a Brazilian sample (median = 92.0) in which 70% of children had severe haemophilia . These data are consistent with the availability of clotting factor concentrates in the countries referenced.…”
Section: Discussionsupporting
confidence: 83%
“…23 The generic measure of activity, the ASK, also provides supplementary information that enables the children in Jamaica to be compared with other studies. The reported mean score of 82.0 for Jamaican children in this study was slightly higher (better) than the mean from a Chinese sample with severe haemophilia (mean = 74.9 during on-demand therapy) 24 and 77.0 in European countries 27 ; and mean Haemo-QoL-A score of 85.6 in the USA. 28 This indicates that there is a large and significant gap in HRQoL between PWH in countries with different access to clotting factor concentrates.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The Canadian Hemophilia Outcomes–Kids Life Assessment Tool (CHO‐KLAT) is a disease‐specific HRQoL instrument validated for use in boys 4‐18 years of age. It has been used in a number of clinical studies and was found to be sensitive to clinically important changes in the setting of the use of factor (F)VIII/FIX concentrates for the management of boys with hemophilia . Pooled CHO‐KLAT data from clinical studies in 9 countries provided a sample size large enough to allow evaluation of the impact of treatment on HRQoL while controlling for confounding relationships.…”
Section: Introductionmentioning
confidence: 99%